Effect of Seed Inoculation with Azotobacter and Soaking in Trace Element Solution on the Growth and Yield of Some Vegetable Crops - BADAWY, FARIDA H.; IMAM, MOSTAFA K. (The Libyan Journal of Agriculture, 2023)
In an attempt to improve growth and yield, seeds of cabbage, cauliflower, onion and lettuce were subjected before sowing to one of the following treatments: (a) soaking in a solution containing the trace elements B, Cu. Mn and Mo; (b) inoculation with isolates of Azotobacter chroococcum (Beijerinck), (c) soaking in the trace element solution and inoculation with Azotobacter. Seeds of these treatments as well as untreated seeds were planted in the field in randomized complete block design and growth of the plants was measured at the time of transplanting and at harvest. Seed soaking depressed the growth of the 4 vegetable crops tested during the seedling stage, but this did not persist at later stages of growth, except for lettuce. Inoculation with Azotobacter significantly improved the growth of cabbage, cauliflower, and onion transplants and showed slight beneficial effect on lettuce. Growth improvement, however did not result in a significant increase in the yields of the tested crops. In another experiment, inoculation of seed tubers of two potato cultivars before sowing with Azotobacter did not increase the yield obtained, number of tubers per plot, or mean weight of tuber.